2007
DOI: 10.1073/pnas.0701771104
|View full text |Cite
|
Sign up to set email alerts
|

Forerunner genes contiguous to RB1 contribute to the development of in situ neoplasia

Abstract: We used human bladder cancer as a model system and the whole-organ histologic and genetic mapping strategy to identify clonal genetic hits associated with growth advantage, tracking the evolution of bladder cancer from intraurothelial precursor lesions. Six putative chromosomal regions critical for clonal expansion of intraurothelial neoplasia and development of bladder cancer were identified by using this approach. Focusing on one of the regions, which includes the model tumor suppressor RB1, we performed all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 31 publications
1
65
0
Order By: Relevance
“…No FGFR3 mutations are reported in CIS 146 . In morphologically 'normal' or dysplastic urothelium adjacent to MIBC, alterations found in the tumour are present, indicating spread of cells from the tumour or tumour development within a field of altered urothelium [147][148][149][150] . Detailed mapping of entire cystectomy specimens reveals that in the absence of detectable abnormality, large macroscopically 'normal' urothelial patches show LOH of specific chromosomal regions.…”
Section: Molecular Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…No FGFR3 mutations are reported in CIS 146 . In morphologically 'normal' or dysplastic urothelium adjacent to MIBC, alterations found in the tumour are present, indicating spread of cells from the tumour or tumour development within a field of altered urothelium [147][148][149][150] . Detailed mapping of entire cystectomy specimens reveals that in the absence of detectable abnormality, large macroscopically 'normal' urothelial patches show LOH of specific chromosomal regions.…”
Section: Molecular Biomarkersmentioning
confidence: 99%
“…Thus, it is envisaged that the development of MIBC involves clonal expansion, within which sub-clones with additional alterations arise (Figure 4). Six critical regions of LOH were identified within one of which, biallelic inactivation of integral membrane protein 2B (ITM2B) and lysophosphatidic acid receptor 6 (LPAR6, also known as P2RY5) were demonstrated 149,151 .…”
Section: Molecular Biomarkersmentioning
confidence: 99%
“…44,45 The detailed analysis of P2RY5 polymorphisms, including germ-line mutations, provides remarkable data in support of potential inherited host susceptibility to the carcinogenic effects of smoking. Mapping of the P2RY5 polymorphisms in normal bladder mucosa demonstrated that this gene, which resides within intron 17 of the RB1 gene, is affected before loss of RB expression during bladder carcinogenesis.…”
Section: Alterations In Forerunner Genes In Patients With Bladder Cancermentioning
confidence: 99%
“…This is based on the concept that these genes are relevant for the development of the initial clonal expansion of in situ urothelial neoplasia. 44 …”
Section: Whole-organ Mapping Of the Bladder Cancer Genomementioning
confidence: 99%
See 1 more Smart Citation